2005
DOI: 10.1108/09513570510627711
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of accruals‐based Crown (government) financial statements in New Zealand

Abstract: PurposeThe aim of this research is to illustrate how a change from cash‐based accounting to accruals‐based accounting in the core public sector of New Zealand occurred.Design/methodology/approachThe grounded theory research strategy is used in a field study setting.FindingsThe findings suggest that there were six antecedents of the change – key people, axial principles, communicating ideas, contextual determinants, ethos, and knowledge. All of these converged to create the synergistic process of change that le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 42 publications
5
51
0
4
Order By: Relevance
“…Data saturation was starting to occur with the 17 th interview signalling that data collection is complete (Kuzel, 1999). Lye et al (2005) explains "data saturation occurs when new data that are collected fit the categories already derived from prior analysis, are repetitive, and no new themes emerge". Two further interviews were conducted then, taking the total number of interviews to 19, to ensure that our judgement of data saturation was reasonable.…”
Section: Methodsmentioning
confidence: 99%
“…Data saturation was starting to occur with the 17 th interview signalling that data collection is complete (Kuzel, 1999). Lye et al (2005) explains "data saturation occurs when new data that are collected fit the categories already derived from prior analysis, are repetitive, and no new themes emerge". Two further interviews were conducted then, taking the total number of interviews to 19, to ensure that our judgement of data saturation was reasonable.…”
Section: Methodsmentioning
confidence: 99%
“…Being a very important management accounting innovation, accrual basis accounting has been viewed as a key innovation in the process of pursuing various NPM principles (Lapsley, 1998;Likierman, 2000;Lye, Perera, & Rahman, 2005). It has been evidenced in many studies that accrual accounting elements have actually been adopted by a considerable number of countries and that they are also considering and willing to implement additional ones mainly in the short-term future (Jones, 2000;Lüder, 2000;Paulsson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…During the literature review, we found that laws, regulations or standards can help to implement IT PM by pressure from outside [14,21,[32][33][34]. In many countries where PM is already implemented there are legal requirements to report and inform -mostly externalstakeholders [45,52,64]. However, these legal requirements do not guarantee that KPIs are not manipulated or collected without accuracy and that PM information is used effectively.…”
Section: Fig 1 Influencing Factors Driving Forces and Barriers Regmentioning
confidence: 99%